2018
DOI: 10.1155/2018/2165627
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of Traditional Birth Attendants on Their Experiences and Roles in Maternal Health Care in Rural Areas of Northern Ghana

Abstract: Background Traditional birth attendants play significant roles in maternal health care in the rural communities in developing countries such as Ghana. Despite their important role in maternal health care, there is paucity of information from the perspective of traditional birth attendants regarding their role on maternal health care in rural areas in Ghana. Objective The aim of this study was to explore and describe the role of traditional birth attendants in maternal health care in the rural areas in Ghana. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 14 publications
3
42
0
Order By: Relevance
“…The findings also affirm the existing documentation that some women in SSA use health facilities for ANC but go on to deliver at home where SBAs are more likely to be absent [13,32]. Notwithstanding, we believe that among other maternal health interventions in the study area, the re-orientation of TBAs in the Upper East region of Ghana to referring or accompanying pregnant women to the health facilities to deliver, instead of conducting the deliveries themselves, might have contributed to the relatively lower proportion of home deliveries noted in this study [33,34].…”
Section: Discussionmentioning
confidence: 72%
“…The findings also affirm the existing documentation that some women in SSA use health facilities for ANC but go on to deliver at home where SBAs are more likely to be absent [13,32]. Notwithstanding, we believe that among other maternal health interventions in the study area, the re-orientation of TBAs in the Upper East region of Ghana to referring or accompanying pregnant women to the health facilities to deliver, instead of conducting the deliveries themselves, might have contributed to the relatively lower proportion of home deliveries noted in this study [33,34].…”
Section: Discussionmentioning
confidence: 72%
“…Majority of the significant others of women cited the need for mothers to go to a health facility to minimize the occurrence of -or-severity of maternal and child health negative outcomes. As cited from prior studies, some felt that they could rely on the knowledge and expertise of TBAs to help them detect a birth-related complication requiring the intervention of a health expert [16,17]. This assumption was found from previous studies to be misleading as it exposes the mother to the likelihood of experiencing adverse negative outcomes (such as; death, loss of the baby, psychological stresses, among others) because of the delays between transferring the mother from the TBA's place to the health facility, as most women are referred in poor clinical state [18].…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organisation (WHO) de nes a traditional birth attendant as "a person who assists the mother during childbirth and initially acquired her skills by delivering babies herself or through apprenticeship to other traditional birth attendants" [9]. Traditional Birth Attendants (TBAs) continue to play a signi cant role in assisting childbirth care services, particularly in rural areas of Ghana [10]. The recent maternal health statistics from Ghana Health Service 2016 report shows that more than 80% of pregnant women had at least one contact with a skilled provider during pregnancy and only 56.2% of deliveries were attended by skilled birth attendants [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that in Ghana, women, traditionally prefer to deliver at home because it is cheaper, and easier as women who deliver at home receive social support from their extended families and do not have to pay much for the delivery services [10,12,13]. Other studies [14][15][16][17] indicate that lack of nancial or economic resources, transportation, and delivery of supplies, lack of coordination and referral between Traditional Birth Attendants at the community level and facilities can all inhibit women from using facility-based services.…”
Section: Introductionmentioning
confidence: 99%